2007
DOI: 10.1007/s00497-007-0060-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization: analysis of early post-fertilization development using cytological and molecular techniques

Abstract: Methods have been developed which enable us to obtain in vitro fusion of pairs of sperm and egg cells, and sperm and central cells of angiosperms. Cultured products of such cell fusions develop progressively into zygotes, embryos and fertile plants, and endosperm, respectively. In vitro fusion of isolated gametes allows precisely timed examination of the earliest developmental processes following fertilization. When cultured, in vitro produced zygotes and primary endosperm cells organize themselves independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 86 publications
0
13
0
1
Order By: Relevance
“…If male germ transmission is successful, one sperm cell fuses with the egg to produce the embryo, and the other fuses with the central cell to produce the nutritive endosperm. Although molecular details are yet incomplete, in vitro experiments suggest that sperm cells, although naturally fusogenic, discriminate and fuse only with egg and central cellswhich constitute the female gametic cells-rather than with synergids, antipodals or somatic cells (Faure et al 1994;Wang et al 2006;Kranz and Scholten 2008;this issue). The idea that cell surface molecules in male gametes may mediate gametic recognition and fusion processes in flowering plants seems a logical conclusion based on studies of preferential gamete fusion (Russell 1985) and is supported by analogy with animal systems.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…If male germ transmission is successful, one sperm cell fuses with the egg to produce the embryo, and the other fuses with the central cell to produce the nutritive endosperm. Although molecular details are yet incomplete, in vitro experiments suggest that sperm cells, although naturally fusogenic, discriminate and fuse only with egg and central cellswhich constitute the female gametic cells-rather than with synergids, antipodals or somatic cells (Faure et al 1994;Wang et al 2006;Kranz and Scholten 2008;this issue). The idea that cell surface molecules in male gametes may mediate gametic recognition and fusion processes in flowering plants seems a logical conclusion based on studies of preferential gamete fusion (Russell 1985) and is supported by analogy with animal systems.…”
Section: Introductionmentioning
confidence: 96%
“…Among factors contributing to difficulties in characterizing molecular determinants of plant sexual reproduction are the relative inaccessibility of sperm and egg cells due to their encasement in gametophyte tissues; however, cell separation technologies for generative and sperm cells have been developed for numerous plant species (Russell 1991;Uchiumi et al 2006) leading the way to molecular approaches to studying these cells (see also Kranz and Scholten 2008;this issue). Metabolite labeling experiments using isolated male germ cells have confirmed that these cells possess transcriptional and translational capabilities independent of the outer pollen vegetative cell (Zhang et al 1993;Blomstedt et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore restrict our comparative review to early molecular fertilization mechanisms in flowering plants and animals, reporting mainly about gamete morphology and function, as well as gamete cross-talk and fusion. Late fertilization events that include prevention of polyspermy, nuclear migration and karyogamy as well as egg activation are compared in the corresponding reviews elsewhere in this issue (Spielman and Scott 2008;Kranz and Scholten 2008;Curtis and Grossniklaus 2008, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome and proteome analyses on isolated egg cells, zygotes and proembryos developing in vitro reveal several genes and proteins that play important roles during the initial phases of embryogenesis in wheat (Sprunck et al 2005;Sz} ucs et al 2006), maize (Okamoto et al 2004Yang et al 2006), tobacco (Ning et al 2006) and rice (Uchiumi et al 2007a). The aim of this research is to model the development of in planta zygotic embryos, which can only be accessed with difficulty (for review, see Kranz and Scholten 2008;Nawy et al 2008;Wang et al 2006). In order to set up a complete and reliable model, in addition to optimal culture systems and molecular research, histological and cytological studies to compare in vitro and in planta embryogenesis will be required.…”
Section: Introductionmentioning
confidence: 99%